2020
DOI: 10.1186/s12935-020-01368-8
|View full text |Cite
|
Sign up to set email alerts
|

Systematic profiling of alternative splicing in Helicobacter pylori-negative gastric cancer and their clinical significance

Abstract: Background: Alternative splicing (AS) may cause structural and functional variations in the protein to promote the proliferation of tumor cells. However, there is no comprehensive analysis of the clinical significance of AS in Helicobacter pylori-negative gastric cancer (HP − GC). Methods: The clinical, gene expression profile data and AS events of 138 HP − GC patients were obtained from the database named the cancer genome atlas. Differently expressed AS (DEAS) events were determined by a comparison of the PS… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
12
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 13 publications
(14 citation statements)
references
References 59 publications
(59 reference statements)
0
12
0
Order By: Relevance
“…Efficient pre-mRNA splicing required both cis-elements and trans-acting regulators, and their dysregulations induce aberrantly spliced molecules, resulting in aberrant expression profiles. Several studies have demonstrated that splicing factors are frequently mutated or dysregulated in GC and pre-mRNA splicing is frequently deregulated in the disease, which may also correlate with prognostic value [ 27 , 28 ]. In addition, we and others have identified the molecular pathways that regulates stem cell marker CD44 variant isoform expression in GC [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…Efficient pre-mRNA splicing required both cis-elements and trans-acting regulators, and their dysregulations induce aberrantly spliced molecules, resulting in aberrant expression profiles. Several studies have demonstrated that splicing factors are frequently mutated or dysregulated in GC and pre-mRNA splicing is frequently deregulated in the disease, which may also correlate with prognostic value [ 27 , 28 ]. In addition, we and others have identified the molecular pathways that regulates stem cell marker CD44 variant isoform expression in GC [ 29 , 30 ].…”
Section: Discussionmentioning
confidence: 99%
“…As the two main components, TIICs and stromal cells were regarded as valuable factors affecting the effect of tumor immunotherapy [ 13 17 ]. It was reported that immune cells, such as T and B cells, macrophages, dendritic cells, monocytes, etc., interacted with tumor cells, were correlated to tumor cell proliferation, metastasis and prognosis [ 18 20 ]. Regulated by Tregs and M2 macrophages, tumor-infiltrating lymphocytes (TILs) were involved in the occurrence and progression of various cancers [ 21 25 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, Chuan Liu et al 20 and Victoria E S Armero et al 21 had determined the prediction model of AS events in Helicobacter pylori-negative cohort and Epstein-Barr virus cohort of GC, respectively. However, the present study depicted the landscape of AS pro les within the entire GC cohort and respectively constructed the risk prediction model strati ed by 7 types of AS.…”
Section: Discussionmentioning
confidence: 99%